2017
DOI: 10.21767/2574-2817.100015
|View full text |Cite
|
Sign up to set email alerts
|

Parental Oral Health Knowledge, Attitude, Practice and Caries Status of Sudanese Cerebral Palsy Children

Abstract: Background: Cerebral palsy (CP) is a set of nonprogressive neuromuscular disorders due to defects in the developing fetal brain, this group of children at risk of dental caries and gingival diseases owing to dietary factors, poor oral hygiene, lack of parental knowledge concerning oral hygiene and problems related to dental management. The study aimed to assess the parental knowledge, attitude and practices of the oral health and caries status of the Sudanese Cerebral Palsy children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
3
4
0
1
Order By: Relevance
“…Parents with higher knowledge scores reported to have signi cantly less dental caries experience and good oral health. The ndings of the present study are in line with previous studies done by Amjad H.Wyne elal and Hadeya M Hamid etal 25 which indicated that strong knowledge of oral health exhibits better oral care practice and more positive attitude towards oral health as mean attitude score and practices signi cantly increases with increase in knowledge as in the present study practices and attitude were better in the parents with higher knowledge scores.…”
Section: Discussionsupporting
confidence: 92%
“…Parents with higher knowledge scores reported to have signi cantly less dental caries experience and good oral health. The ndings of the present study are in line with previous studies done by Amjad H.Wyne elal and Hadeya M Hamid etal 25 which indicated that strong knowledge of oral health exhibits better oral care practice and more positive attitude towards oral health as mean attitude score and practices signi cantly increases with increase in knowledge as in the present study practices and attitude were better in the parents with higher knowledge scores.…”
Section: Discussionsupporting
confidence: 92%
“…Assessment of socio-demographic characteristics of spastic CP childrenThe results show that about two-thirds (65.2%) of spastic CP children were school-age. This result is supported by other studies reporting SP children aged 2-10 years [22], and aged 2-6 years [20]. The result is in That level of education, age of caregiver, and height of the spastic CP were factors associated with the caregiver's knowledge and shows a highly significant p-value of 0.002.…”
Section: Resultssupporting
confidence: 84%
“…The researchers constructed a questionnaire consisting of two parts: part one assessed the socio-demographical characteristics of caregivers and CP children, such as the age of the caregiver, marital status, occupation, level of education, type of family, economic status, and type of delivery, and part two the second consisted of 20 questions related to caregiver's knowledge regarding spastic CP. A three-point scale was used (0 for bad knowledge, 1 for fair knowledge, and 2 for good knowledge) and overall knowledge was categorized into three groups: bad knowledge (0-6), fair knowledge (7-13), and good knowledge (14)(15)(16)(17)(18)(19)(20). Data were gathered through face-to-face interviews during the home visits and the investigator filled out the questionnaire tool.…”
mentioning
confidence: 99%
“…Additionally, they will also refrain from bad behaviours that can bring dental caries like drinking alcohol and chewing khat 6 and healthy behaviours like tooth brushing, flossing, and avoiding sweet food practice. 6,8,23,24 Another important factor associated with dental health problems is tooth brushing. This study showed that tooth brushing practice reduced dental health problems by 76% compared with individuals who did not brush their teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they will also refrain from bad behaviours that can bring dental caries like drinking alcohol and chewing khat 6 and healthy behaviours like tooth brushing, flossing, and avoiding sweet food practice. 6 , 8 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%